Global Trends and Burden of Diabetes: A Comprehensive Review of Global Insights and Emerging Challenges - VB, Anushree; Jha, Deepak Kumar; Bhattacharjee, Soham (Current Journal of Applied Science and Technology, 2025)
Background: Diabetes mellitus is a growing global health challenge, with its prevalence rising rapidly. The increase in diabetes population has been notably higher in lower and middle-income nations with resulting in inequalities in the global disease burden. Aim: This review is to provide a comprehensive analysis of the global trends, risk factors, and burden of diabetes while identifying emerging challenges in its prevention and management. Materials and Methods: This review is based on the widely conducted analysis of peer‑reviewed literature, reports on the health of countries across the world, and epidemiological data published by the authoritative bodies like the WHO, IDF, and CDC. Research on the topic was done in a systematic manner through the primary databases, including PubMed, Scopus, and Google Scholar, in search of relevant reports and studies. Findings: Diabetes mellitus is a rapidly growing disease with prevalence expected to rise from 537 million adults today to 783 million by 2045. Type 2 diabetes accounts for over 90% of cases, with key risk factors including genetic predisposition, poor diet, physical inactivity, obesity, urbanisation, and an ageing population. The condition leads to severe health complications such as cardiovascular diseases, kidney failure, blindness, and amputations, imposing a significant economic burden that exceeds $1 trillion annually. Emerging challenges include increasing cases among children and adolescents, disparities in healthcare access, the impact of climate change and urbanisation, and limited availability of advanced diabetes technologies. Conclusion: The emerging diabetes epidemic requires not just population-level-related provisions but also realistic interventions at different points. The state ought to introduce policies that encourage healthy nutritional standards, physical exercise and urban design that encourages active lifestyles, as well as imposing taxes or control over unhealthy food. The healthcare providers must increase screening measures to identify the disease in the early stages, make the necessary medications and devices like glucose monitors and insulin, and diabetes education available, at affordable costs, in the primary care setting.